إشكالية العضوية الكاملة لفلسطين في الأمم المتحدة والبدائل الممكنة - العمري, حكيم (University of Eloued جامعة الوادي, 2020)
يتناول البحث البدائل القانونية التي يمكن من خلالها الوصول إلى العضوية الكاملة لدولة فلسطين في الأمم المتحدة على ضوء رفع التمثيل الفلسطيني إلى دولة غير عضو بصفة مراقب، وفي ضل استخدام الولايات المتحدة الأمريكية حق النقض "الفيتو" ضد أي مشروع قرار لرفع مكانة فلسطين لدولة كاملة العضوية. وهذه البدائل نابعة من روح ومقاصد ميثاق الأمم المتحدة، ومن الممارسة الدولية منها تكرار الطلب لمجلس الأمن وتفعيل المادة137، أو تفعيل القرار377 "الاتحاد من اجل السلام"، إلى جانب زيادة عدد الدول التي تعترف بدولة فلسطين. الكلمات المفتاحية: دولة فلسطين، البدائل القانونية، العضوية الكاملة، مجلس الأمن، الجمعية العامة. Summary: The study deals with legal alternatives through which the full membership of the State of Palestine in the United Nations can be achieved in the light of the lifting of Palestinian representation to a non-member State as an observer, and the veto by the United States of America against any draft resolution to raise the status of Palestine to a full-fledged state. Alternatives stem from the spirit and purposes of the Charter of the United Nations and international practice, such as repeating a request to the Security Council, activating Article 137, activating Resolution 377, Union for Peace, and increasing the number of states that recognize the state of Palestine. Keywords ; state of Palestine, legal alternatives, full membership, Security Council, General Assembly.
The question of the full membership of Palestine in the United Nations and possible alternatives.
مقال
Keywords: دولة فلسطين،البدائل القانونية،العضوية الكاملة مجلس الامن الجمعية العامة.; state of Palestine, legal alternatives, full membership, Security Council, General Assembly